Analysis of Factors that Influence Consumer Satisfaction in Zest Chicken Restaurant Sumenep - Rahman, Sindi Arista; Muhaimin, Abdul Wahib; Toiba, Hery (Jurnal Social Economic of Agriculture, 2024)
The rapid growth in the number of fast food restaurants in Sumenep City has resulted in a high level of competition so that every restaurant needs to create consumer satisfaction both from product and service elements. This research aims to analyze the factors that contribute to consumer purchasing decisions and analyze consumer satisfaction with the performance of the Zest Chicken-Geprek Lek Djo Restaurant, Sumenep City. The research location was carried out purposively and the sample method used was Accidental Sampling, totaling 100 people. The data used in this research are primary data and secondary data. The data analysis method uses Factor Analysis, Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The research results show that there are four factors formed consisting of 18 attributes. Two attributes that are not included in the formation of factors are Help to Help Choose Products and Individual Attention. Overall the level of consumer satisfaction with restaurant performance is categorized as satisfied because the CSI value is 75.20%. However, the attributes that need to be prioritized in improving performance are the attributes in the first quadrant, namely speed of presenting products, comfortable operating hours, greetings and thanks by the waiter. The implications of this research are that restaurants can improve service attributes, namely the friendliness of employees in Quadrant I and add employees